"Work-life balance of working women: a review of literature" - Neha Poddar; Prakash Divakaran (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The main aim of this research is to evaluate the constant improvement of the capabilities of women managers to manage and properly handle the key issues and challenges that arise at the time of management of her career and family life. The researcher reviews the previous research papers and studies for this purpose research collected data from secondary sources like research journals, books, magazines, peer-reviewed journals etc. This study indicated that the number of different variables that are affected on the role of women in the encounter with various challenges arises in balancing career and family responsibilities. These variables are most important for deciding the key challenges of women managers and their dual role of balancing career and family responsibilities.